Profitability, Earnings Management, and Corporate Social Responsibility in Environmental Accounting Moderates Good Corporate Governance - Taufiq, Abd Rohman; Srijani, Ninik; Aisyah, Siti; Widura, Wiko (AKRUAL: Jurnal Akuntansi, 2025)
Backgrounds: Taxes as a source of funding to increase economic growth and national development. Objectives: This study aims to determine the effect of profitability, earnings management, and Corporate Social Responsibility on environmental accounting moderating Corporate Governance. Methods: The population of this study is manufacturing companies listed on the Indonesia Stock Exchange for the period 2021-2024. The sample of this study used a purposive sampling technique totaling 196 companies. The data analysis method used multiple regression analysis and moderated regression analysis. Results: The results of this study indicate that 1) profitability affects environmental accounting, 2) earnings management does not affect environmental accounting, 3) Corporate Social Responsibility does not affect environmental accounting, 4) Corporate Governance cannot moderate profitability on environmental accounting. 5) Corporate Governance can moderate earnings management on environmental accounting, and 6) Corporate Governance can moderate Corporate Social Responsibility on environmental accounting.